Glorified Image, Gloomy Life: Diversified Perceptions and The Transformation in nature of Migration in Bangladeshi Villages - Mahima Ferdousy, Mithila (South Asian Journal of Social Sciences and Humanities, 2024)
Migration refers to the movement of people from their origin to another place for diversified reasons. The glorified image and good life expectations are a matter of discussion whenever it comes to migration but the gloomy sides, transforming perceptions in this migration issue, are still in the shade in Bangladeshi Villages. This article examined the nature of migration and prevailing multiple perceptions and the transformation in these perceptions over decades in Shakhail, Uladab, And Mirkutiya villages located in Tangail District, Dhaka, Bangladesh. This article addresses migration and growth, how the young perceive "bidesh" and how family economic progress affects migration patterns. It is also concerned with the process of materiality determining status. Psychological breakdown, seclusion, and separation are also discussed in this article with relevant case studies. I have Identified various perceptions, which are the collective perceptions of different people from these village communities. In addition, I have tried to predict the future of these villages with the help of Lee’s push-pull theory with relevant narrative analysis.